Water Stress Impacts on Grapevines (Vitis vinifera L.) in Hot Environments: Physiological and Spectral Responses - Alessia Cogato; Shaikh Yassir Yousouf Jewan; Lihua Wu; Francesco Marinello; Franco Meggio; Paolo Sivilotti; Marco Sozzi; Vinay Pagay (Agronomy, 2022)
The projected increase in temperature and water scarcity represents a challenge for winegrowers due to changing climatic conditions. Although heat and drought often occur concurrently in nature, there is still little known about the effects of water stress (WS) on grapevines in hot environments. This study aimed to assess whether the grapevine’s physiological and spectral responses to WS in hot environments differ from those expected under lower temperatures. Therefore, we propose an integrated approach to assess the physiological, thermal, and spectral response of two grapevine varieties (Vitis vinifera L.), Grenache and Shiraz, to WS in a hot environment. In a controlled environment room (CER), we imposed high-temperature conditions (TMIN 30 °C–TMAX 40 °C) and compared the performance of well-watered (WW) and WS-ed potted own-rooted Shiraz and Grenache grapevines (SH_WW, SH_WS, GR_WW, and GR_WS, respectively). We monitored the vines’ physiological, spectral, and thermal trends from the stress imposition to the recovery after re-watering. Then, we performed a correlation analysis between the physiological parameters and the spectral and thermal vegetation indices (VIs). Finally, we looked for the best-fitting models to predict the physiological parameters based on the spectral VIs. The results showed that GR_WS was more negatively impacted than SH_WS in terms of net photosynthesis (Pn, GR-WS = 1.14 μmol·CO2 m−2·s−1; SH-WS = 3.64 μmol·CO2 m−2·s−1), leaf transpiration rate (E, GR-WS = 1.02 mmol·H2O m−2·s−1; SH-WS = 1.75 mmol·H2O m−2·s−1), and stomatal conductance (gs, GR-WS = 0.04 mol·H2O m−2·s−1; SH-WS = 0.11 mol·H2O m−2·s−1). The intrinsic water-use efficiency (WUEi = Pn/gs) of GR_WS (26.04 μmol·CO2 mol−1 H2O) was lower than SH_WS (34.23 μmol·CO2 mol−1 H2O) and comparable to that of SH_WW (26.31 μmol·CO2 mol−1 H2O). SH_WS was not unaffected by water stress except for E. After stress, Pn, gs, and E of GR_WS did not recover, as they were significantly lower than the other treatments. The correlation analysis showed that the anthocyanin Gitelson (AntGitelson) and the green normalised difference vegetation index (GNDVI) had significant negative correlations with stem water potential (<semantics>Ψ</semantics>stem), Pn, gs, and E and positive correlation with WUEi. In contrast, the photochemical reflectance index (PRI), the water index (WI), and the normalised difference infrared index (NDII) showed an opposite trend. Finally, the crop water stress (CWSI) had significant negative correlations with the <semantics>Ψ</semantics>stem in both varieties. Our findings help unravel the behaviour of vines under WS in hot environments and suggest instrumental approaches to help the winegrowers managing abiotic stress.